Moving people in Ethiopia : development, displacement & the state - Pankhurst, Alula, 1962-; Piguet, François (Boydell & Brewer, 2009)
Development worldwide has increasingly involved displacement. Ethiopia is no exception; population displacement resulting from development as well as conflict, drought and conservation has been on the increase since the 1960s. The recent history of conflict in the Horn of Africa has led to large-scale population movements of refugees, returnees, internally displaced groups and demobilized soldiers. The context of drought and food insecurity in the mid-1980s and again in the early 2000s added a further rationale and impetus for organizing state-led resettlement programmes. This book brings together for the first time studies of the different types of development, conflict and drought induced displacement in Ethiopia, and analyses the conceptual, methodological and experiential similarities, overlaps and differences between these various forms. ALULA PANKHURST is an independent researcher and a member of the Forum for Social Studies; FRANCOIS PIGUET is a lecturer on the masters course of Advanced Studies in Humanitarian Action at the Geneva University. Published in association with the Centre Francais des Etudes Ethiopiennes (CFEE).